A STUDY TO EVALUATE THE EFFECTIVENESS OF ANULOM-VILOM TECHNIQUES ON REDUCTION OF ANXIETY AMONG PATIENTS WITH DIABETES MELLITUS ADMITTED IN SELECTED HOSPITAL DHARWAD (Journal of Pharmaceutical Negative Results, 2022)
Anlom Vilom is one of the most effective pranayama. It modulates anxiety responses to and in turn reduces the complex health problems arising due to anxiety. Anlom vilom is found useful in diabetes as alternate nostril breathing has calming effects on the nervous system, facilitating homeostasis. Knowing the background, the study undertaken to evaluate the effectiveness of anlom-vilom techniques on reduction of anxiety among patients with diabetes mellitus admitted in selected hospital Dharwad.The objectives of the study are to:• Assess the level of anxiety among patients with type 2 diabetes.• Evaluate the effectiveness of Anlom-Vilom technique on reduction of anxiety among diabetes patients.• Find an association between pre-intervention mean level of anxiety among type 2 diabetes and selected demographic variable.Conceptual framework: selected for this study was based on modified Learning Bandura’s Theory. Methods: The Pre experimental with one group pre and post-test design was adopted for the present study. The sample consisted of 40 Type 2 diabetes patients selected by non-probability purposive sampling technique. The tool comprised of 2 section namely demographic Proforma and modified Beck anxiety scale and analyzed by using descriptive and inferential statistics appropriate to achieve set of objectives. Results: Maximum 15(37.5%) respondents belong to age between 40-50 years. Majority of the respondents 26(65%) of respondents were males .35 (87.5%) of respondents were married. Maximum of 16(40%) belonged to primary schooling. Majority of 36(90%) had joint family .Maximum of 11(27.5%) were skilled workers. Majority 17(42.5%) had 5000 Rs monthly income and majority 21(52.5%) were on mixed diet. Interpretation and conclusion: Based on the findings of the study anulom vilom technique was effective on reduction of anxiety among patients with type 2 diabetes mellitus.